Suppose a function satisfies the system of equations above, find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since u ( 0 , y ) = e − y 2 , we can assume that u ( x , y ) = e v ( x ) − y 2 . Then we have:
y ∂ x ∂ u + x ∂ y ∂ u y d x d v e v ( x ) − y 2 − 2 x y e v ( x ) − y 2 ⟹ d x d v v ( x ) v ( 0 ) ⟹ v ( x ) ⟹ u ( x , y ) u ( 1 , 2 ) = 0 = 0 = 2 x = ∫ 2 x d x = x 2 + C = 0 + C = 0 = x 2 = e x 2 − y 2 = e 1 2 − 2 2 = e − 3 ≈ 0 . 0 4 9 8 where C is the constant of integration. ⟹ C = 0